2021
DOI: 10.1026/0012-1924/a000260
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich von Intelligenztestleistungen bei monolingualen und bilingualen Kindern und Jugendlichen in den Intelligence and Development Scales–2 (IDS-2)

Abstract: Zusammenfassung. Die Studie untersucht Mittelwertdifferenzen bei Monolingualen und Bilingualen in der allgemeinen Intelligenz sowie 7 Faktoren mit je 2 Untertests mit den Intelligence and Development Scales-2 (IDS-2; Grob & Hagmann-von Arx, 2018 ). Die Stichprobe besteht aus je 132 gepaarten monolingualen, simultan bilingualen und sukzessiv bilingualen Kindern und Jugendlichen der Normierungs- und Validierungsstichprobe ( MAlter = 12.34, SDAlter = 4.44; 48 % Jungen). In einer einfaktoriellen Varianzanalyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…These findings are for the most part in line with the current research [ 14 , 15 , 16 , 17 , 18 , 37 ], postulating that the average levels of performance of simultaneous bilinguals on verbal tasks are more similar to monolinguals than to sequential bilinguals. For this reason, it may be suggested that language acquisition in children who grow up speaking two languages from birth may be very similar to that of monolinguals, as the two separate linguistic systems of simultaneous bilinguals are closely linked.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are for the most part in line with the current research [ 14 , 15 , 16 , 17 , 18 , 37 ], postulating that the average levels of performance of simultaneous bilinguals on verbal tasks are more similar to monolinguals than to sequential bilinguals. For this reason, it may be suggested that language acquisition in children who grow up speaking two languages from birth may be very similar to that of monolinguals, as the two separate linguistic systems of simultaneous bilinguals are closely linked.…”
Section: Discussionsupporting
confidence: 91%
“…Schweizer et al [ 37 ] investigated differences among monolinguals, simultaneous bilinguals, and sequential bilinguals regarding general intelligence and seven factors with two subtests each provided by the Intelligence and Development Scales—2 (IDS—2, [ 38 ]). Based on their sample, including children and adolescents aged 5 to 20, the results indicated lower scores for sequential bilinguals on general intelligence, verbal reasoning, and verbal long-term memory when compared to monolinguals and simultaneous bilinguals.…”
Section: Introductionmentioning
confidence: 99%